FLAVONOID BIOSYNTHESIS GENES IN WHEAT - E. K. Khlestkina; O. Y. Shoeva; E. I. Gordeeva (Вавиловский журнал генетики и селекции)
The biosynthesis of flavonoid compounds is one of the best-studied metabolic pathways in plants. The researchers’ attention to the biochemical, physiological and genetic aspects of flavonoid biosynthesis is associated primarily with the wide range of their biological properties. In addition, the flavonoid biosynthesis gene system is an excellent genetic model. Owing to the development of molecular and genomic methods in recent years, considerable progress is made in the understanding of the molecular and genetic mechanisms underpinning flavonoid biosynthesis in bread wheat (Triticum aestivum L.). This article provides a brief overview of the results of research in the structural and functional organization of flavonoid biosynthesis genes in wheat and its relatives.